Analyzing the Influence of Job Stress on Road Construction Professionals in Bagmati Province, Nepal - Adhikari, Dinesh; Adhikari, Riwaj; Shrestha, Sanjeev (NPRC Journal of Multidisciplinary Research, 2025)
Background: This study investigates job stress and its impact on professionals working in road construction across Bagmati Province, Nepal. A cross-sectional survey was conducted with 159 participants, including project managers, civil engineers, sub-engineers, supervisors, and site in-charges, recruited through non-probabilistic convenience sampling. The questionnaire employed validated scales to measure anxiety, fatigue, depression, dissatisfaction, and self-esteem, with reliability confirmed by Cronbach’s alpha ranging from 0.75 to 0.89. Descriptive statistics identified work overload, low wages, and poor work environment as primary stressors. Inferential analysis through independent samples t-tests and Pearson correlation examined relationships between variables. Low self-esteem was found not to significantly predict anxiety, fatigue, depression, or dissatisfaction. The study highlights nuanced satisfaction levels with job roles and emphasizes socio-political stressors unique to the Nepalese construction context. Recommendations for stress management programs are provided, underscoring the need for organizational and individual interventions. Limitations of convenience sampling and study scope are noted, with directions for future longitudinal and comparative research.Objectives: This study aims to identify and analyze the primary causes of stress experienced by professionals working in the road construction sector in Bagmati Province, and to examine the effects of this stress on their mental health, job satisfaction, and overall work performance. Additionally, the study aims to explore effective stress management strategies and recommend practical interventions—such as improved planning, better communication, increased salary, and enhanced support systems—to help mitigate stress and improve the well-being and productivity of construction workers. Methods: The study used a mixed- methods approach and t-tests to analyze the relationships between stress factors and their effects such as anxiety, fatigue, depression, and job dissatisfaction. To ensure reliability, Cronbach’s alpha was used to validate the measurement scales. Participants with exceptional conditions or who did not consent were excluded, allowing for a focused assessment of occupational stress and its impact on the construction sector.Findings: The study found that road construction workers in Bagmati Province face significant stressors such as heavy workloads, long hours, poor working conditions, lack of support, inadequate safety equipment, unfair treatment, low salaries, and social conflicts. These factors negatively affect their mental health, job satisfaction, and performance, leading to higher absenteeism and turnover. While low self-esteem correlated with negative outcomes like anxiety and fatigue, it was not a significant predictor. Workers expressed a preference for stress management strategies including better planning, increased pay, clear responsibilities, and improved communication to alleviate workplace stress.Novelty: It Systematically explores on the influence of stress among professionals in the road construction sector within Nepal’s Bagmati Province, a context that has been underexplored in existing research. Unlike many prior studies centered on more developed industries or other countries, this research highlights unique stressors such as social-political conflicts, inadequate safety measures, and local community interactions that impact construction workers in a rapidly developing economy. Additionally, the study integrates both psychological factors and practical workplace challenges, providing a comprehensive analysis of stress and its effects on mental health, job satisfaction, and performance. Its recommendations for tailored stress management strategies address the specific needs of construction professionals in Nepal, filling a critical gap in occupational health literature in the region.